THE INFLUENCE OF SERVICESCAPE, SOCIAL MEDIA MARKETING, AND DESTINATION IMAGE ON REVISIT INTENTION AT LANGSA CITY FOREST PARK TOURISM OBJECTS - Siti Zulaikha; Sugih Arto; Syafrizal Helmi Situmorang (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The natural tourist attraction currently developing in Langsa City is Langsa City Forest Park or also known as Protected Forest. This research is causal associative research. The author conducted research at City Forest Park which is located at Gp. Paya Bujok Seuleumak Village Public Housing, Langsa Baroe District, Langsa City. The time of the research carried out by researchers was from May 2024 to June 2024. The population in this study were visitors to the Langsa City Forest Tourism Object. In this study, there were 35 indicator items. Thus, 175 respondents will be taken. With the results, Servicescape has a positive and significant effect on Revisit Intention at the Langsa City Forest Park Tourist Attraction. Social Media Marketing has a positive and significant effect on Revisit Intention at the Langsa City Forest Park Tourist Attraction. Destination Image has a positive and significant effect on Revisit Intention at the Langsa City Forest Park Tourist Attraction. Servicescape, Social Media Marketing, Destination Image have a positive and significant effect on Revisit Intention at the Langsa City Forest Park Tourist Attraction.